DOMAIN TRANSFORMATION TO OBTAIN TIME-DOMAIN ELECTROMAGNETIC RESPONSE FROM FREQUENCY-DOMAIN RESPONSE IN CASE OF CIRCULAR LOOP SOURCE - Muaffi Wikan, Hasnan
Frequency-Domain Electromagnetic (FDEM) and Time-Domain Electromagnetic (TDEM) are parts of the Controlled-Source Electromagnetic Method (CSEM). In order to obtain the time-domain electromagnetic response from an underground earth layer, inverse Fourier transforms can be done to frequency-domain electromagnetic responses. One of the sources used for measurement is a loop on the earth surface. Analytic method for generating time-domain responses from a loop source, where the receiver is placed at the center of the loop, is only available for homogenous half-space cases, but there are computational methods available that can calculate the frequency-domain responses for various arrangements of source and receiver for multilayer models. “EMLCLLER_Corr”, a program for generating frequency-domain responses with circular loop source for various receiver positions, is used to obtain frequency-domain responses for homogenous-half space and multilayer cases. Transformation of the frequency-domain data using numeric inverse Fourier transform is done to obtain the time-domain responses. It is found that from the comparison between the analytic method and the transformation results for the homogenous half-space case, the shape of the inverse Fourier transform agrees with the analytic method for the early time, but fluctuates for the late time.